2020
DOI: 10.30548/vascfail.3.2_59
|View full text |Cite
|
Sign up to set email alerts
|

Novel inhibitory effects of dotinurad, a selective urate reabsorption inhibitor, on urate crystal-induced activation of NLRP3 inflammasomes in macrophages

Abstract: Background: When macrophages are primed by lipopolysaccharides, mono sodium urate (MSU) crystals activate NLRP 3 inflammasomes and promote IL-1β and IL-18 production after phagocytosis of MSU. It was previously reported that anti-IL-1β antibodies suppress symptoms of gout and the occurrence of cardiovascular disease. Thus, inhibition of NLRP3 inflammasomes, which produce IL-1β and IL-18, may be a novel therapeutic strategy against these diseases. Purpose: To reveal the effects of dotinurad, a selective urate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Dotinurad is a SURI (Fuji Yakuhin, Chiba, Japan) that was approved in Japan 2020 ( Taniguchi et al, 2019 ). In vitro studies reported that dotinurad also inhibits the NLRP3 inflammasome ( Taufiq et al, 2020 ). Two phase 2 studies demonstrated dose-dependent urate-lowering effects in subjects taking 0.5–4 mg/d of dotinurad ( Kuriyama, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dotinurad is a SURI (Fuji Yakuhin, Chiba, Japan) that was approved in Japan 2020 ( Taniguchi et al, 2019 ). In vitro studies reported that dotinurad also inhibits the NLRP3 inflammasome ( Taufiq et al, 2020 ). Two phase 2 studies demonstrated dose-dependent urate-lowering effects in subjects taking 0.5–4 mg/d of dotinurad ( Kuriyama, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The precise mechanisms responsible for those findings are still unclear. Taufiq et al showed that dotinurad suppressed monosodium urate-induced activation of nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing protein 3 inflammasomes in mouse macrophages [ 36 ]. A recent experimental study also revealed that dotinurad ameliorated insulin resistance and hepatic steatosis through the suppression of reactive oxygen species (ROS) production and brown adipose tissue whitening in high-fat diet-induced obese mice [ 37 ].…”
Section: Discussionmentioning
confidence: 99%